3D Structure Modeling of Catalase Enzyme from Aspergillus fumigatus - Vivek Dhar Dwivedi; Shiv Bharadwaj; Aman Chandra Kaushik; Sarad Kumar Mishra (Open Journal of Proteomics and Genomics - Peertechz Publications, 2016)
The respiratory diseases in humans, such as aspergilloma, allergic bronchopulmonary aspergillosis and invasive aspergillosis are caused by the fungal pathogen Aspergillus fumigatus (A. fumigatus) The enzyme catalase of A. fumigatus provides a putative virulence to this fungal pathogen against the toxic effects of human hydrogen peroxide, which they cleave into water and molecular oxygen. The 3-D tructure of this protein in A. fumigatus is not known, while it is very important for understanding the molecular mechanism of action of this enzyme and development of new drugs for various respiratory diseases. This article proposes the 3-D structure of catalase enzyme from A. fumigatus which has been predicted and validated using different computational programs. Based on the percentage of residue occurrence in helical, strand and loop regions, four structural domains have been identifi ed in the modeled structure. The structure and function relationship for all identifi ed structural domains have been also described. This study will be helpful for in silico drug discovery against the virulence nature of Aspergillus fumigatus.